2019
DOI: 10.1111/odi.13015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age on oral squamous cell carcinoma: A longitudinal cohort study of 2,782 patients

Abstract: Background:The purposes of this study were to assess the influence of age on oral squamous cell carcinoma patients and sought to analyze the reasons that may contribute to this difference.Methods: This study enrolled 2,782 patients included 2,443 patients in a retrospective cohort to find the influence of age and 339 patients in a prospective cohort to testify these findings. The patients were divided into young age-group (≤40 years old), moderate age-group (41-75 years old), and advanced age-group (>75 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
3
24
2
Order By: Relevance
“…Head and neck squamous cell carcinoma (HNSCC), a common type of cancer, can cause both psychological and physiological damage to patients 1 . Tumor metastasis is the main reason for poor outcome 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC), a common type of cancer, can cause both psychological and physiological damage to patients 1 . Tumor metastasis is the main reason for poor outcome 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC), representing a group of tumors in the larynx, pharynx and oral cavity, is the sixth most common cancer in the world, with ~500,000 new cases worldwide each year ( 1 , 2 ). Among these cases, oral squamous cell carcinoma (OSCC) and laryngeal squamous cell carcinoma (LSCC) have a high incidence, especially in China ( 3 , 4 ), exhibiting high morbidity and mortality rates ( 5 ). According to GLOBOCAN 2012, the incidence and mortality rate of laryngeal cancer in China was 1.1/100,000 and 0.7/100,000, compared with the global incidence and mortality rate of which was 2.1/100,000 and 1.1/100,000, respectively ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increase in the overall incidence of oral tongue squamous cell carcinoma (OTSCC) in young patients 1,2,3 at a frequency that ranges from 0.13 to 12.76% among all cases of OTSCC. 2,3,4,5,6 Males are more frequently affected by OTSCC, regardless of age, although recent studies have indicated an increase in incidence among young women. 1,3 The etiopathogenesis of OTSCC in young patients is still widely discussed in the scientific literature because many patients are not exposed to the main risk factors, such as smoking and/or alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4,5,6 Males are more frequently affected by OTSCC, regardless of age, although recent studies have indicated an increase in incidence among young women. 1,3 The etiopathogenesis of OTSCC in young patients is still widely discussed in the scientific literature because many patients are not exposed to the main risk factors, such as smoking and/or alcohol consumption. 1,3,4 Heredity 4 and human papillomavirus (HPV) infection have been suggested to play a role in this age group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation